2004
DOI: 10.1001/archinte.164.13.1451
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Knowledge, Attitudes, and Beliefs of House Staff Physicians From Various Specialties Concerning Antimicrobial Use and Resistance

Abstract: This survey (1) revealed that house staff are aware of the importance of antimicrobial resistance and believe better antimicrobial use will help this problem and (2) demonstrated differences between specialties with respect to antimicrobial use and knowledge. House staff at our hospital have suboptimal knowledge about antimicrobials, and this knowledge did not increase appreciably over the course of their training. Antimicrobial education is needed and is likely to be well received by house staff physicians in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
163
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 31 publications
30
163
5
Order By: Relevance
“…This relates to the surveys from other countries in which the antibiotic guidelines ranked high by the participants with a demand to develop local antibiotic guidelines (García et al, 2011;Guerra et al, 2007). Similarly, when prescribing antibiotics, there was a little tendency to consult colleagues (Bennish and Khan, 2010;Srinivasan et al, 2004). Today, several countries like Netherlands and Britain are concentrating on public education so as to promote the rational use of antibiotics in the local community in order to minimize the development of resistance to antibiotics (Davey et al, 2002;Stille et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relates to the surveys from other countries in which the antibiotic guidelines ranked high by the participants with a demand to develop local antibiotic guidelines (García et al, 2011;Guerra et al, 2007). Similarly, when prescribing antibiotics, there was a little tendency to consult colleagues (Bennish and Khan, 2010;Srinivasan et al, 2004). Today, several countries like Netherlands and Britain are concentrating on public education so as to promote the rational use of antibiotics in the local community in order to minimize the development of resistance to antibiotics (Davey et al, 2002;Stille et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Such type of improvement always requires vital changes in medical doctor's behaviour through their awareness and perceptions regarding antibiotic resistance (Wester et al, 2002;Giblin et al, 2004;Srinivasan et al, 2004). Medical doctors may modify their practice only when their attitudes, skills, beliefs and knowledge are integrated with each other potentially resulting in a decrease in antibiotic resistance (Wester et al, 2002;Giblin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…20 Several surveys about antimicrobial resistance have been conducted with different types of healthcare workers, including medical students, residents, and attending physicians (Table 6). [21][22][23][24][25] These previous studies have found that 87% to 97% of respondents viewed resistance as a national problem while fewer (55% to 93%) viewed resistance as a local problem. 17,19,[21][22][23][24] In contrast, we found that the vast majority of respondents at our institution agreed that MDR-GNB infections were a serious problem in ICUs both in the U.S. and at our medical center.…”
Section: Discussionmentioning
confidence: 99%
“…21,24,25 As noted in previous studies and our study, most healthcare providers believed that excess use of antimicrobials was a cause of resistance, 24,25 but fewer believed that antimicrobials were overused in the hospitals in which they worked. 22,23 Our survey uncovered a substantial knowledge gap which may delay appropriate implementation of transmission precautions and thus facilitate transmission of multidrugresistant organisms. 4 Among ICU providers, only 74% agreed that implementing Contact Isolation for patients harboring MDR-GNB could decrease resistance and even fewer respondents were aware of the MDR-GNB definition used to initiate such precautions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation